„Playing hurt“: der Umgang jugendlicher Leistungssportler mit Gelenkschmerzen - Diehl, Katharina; Schneider, Sven; Mayer, Jochen; Thiel, Ansgar (Der Schmerz, 2019)
BackgroundUp to now, the investigation of joint pain in adolescents, especially in adolescent elite athletes, has been neglected. This is critical because the musculoskeletal system is still in growth and consecutive trauma and irreversible damage can result.ObjectivesTo shed light into the research area of joint pain in elite adolescent athletes, we studied the willingness to compete while having joint pain as part as the phenomenon of “playing hurt”. Our aim was to describe which athletes are more willing to compete in spite of joint pain and which individual and sport-specific characteristics are associated with it.Materials and methodsWe used data of the nationwide GOAL study which included 1138 adolescent athletes from 51 Olympic sports (56.1% male, 14-18 years of age).ResultsAltogether, 43.8% of the German elite adolescent athletes were willing to participate in competition in spite of joint pain. The willingness was higher among female athletes, athletes with a higher number of competitions, athletes living in a boarding school, and athletes in weight-dependent sports.ConclusionsThe fact that more than four out of ten adolescent elite athletes are willing to compete despite joint pain is alarming because joint pain can have severe long-term health consequences. It is important that trainers, managers and physicians offer assistance in the treatment of joint pain and support them as much as possible in therapy and pain management. The overarching aim should be to prevent irreversible damage as well as a premature end of the sports career.
Online publiziert: 2. Januar 2018
Gesehen am 05.12.2019